New approach for routing in mobile ad‐hoc networks based on ant colony optimisation with global positioning system. Issue 3 (1st September 2013) - Karia, Deepak C.; Godbole, Vaibhav V.
Abstract : The field of mobile ad‐hoc networks (MANETs) has gained an important part of the interest of researchers and become very popular in past few years. MANETs can be used to set up a temporary mean of communication by having nodes behave as hosts and routers, with packets hopping between nodes to reach the destination node. This makes MANET suitable for rapid deployment, but because of the dynamic changes in network configurations, quickly finding the optimum route is difficult. In this study, the authors propose a biology‐inspired ant routing protocol based on ant colony optimisation called as optimised antnet global positioning system, which is based on GPS and mobile software agents modelled on ants for routing in ad‐hoc networks. The authors compare the performance of the authors protocol with Antnet, ad‐hoc on‐demand distance vector, Dynamic Source Routing (DSR) and Ad‐hoc On Demand Multipath Distance Vector (AOMDV) protocols with respect to end‐to‐end delay, average throughput, packet delivery ratio and route cost.